Tamoxifen Inhibits Induction of the Mitochondrial Permeability Transition by Ca2+and Inorganic Phosphate - Custódio, José B. A. (1998)
Tamoxifen (TAM) is a synthetic, nonsteroidal antiestrogenic agent that is widely prescribed in the treatment of estrogen-dependent neoplasias, including breast cancer. The mechanism of action has yet to be defined, but likely is independent of estrogen receptor binding. In light of its high lipophilicity and peroxyl radical scavenging activities, we hypothesized that TAM might be an effective inhibitor of the mitochondrial permeability transition (MPT), which is widely implicated in the mechanisms of chemical-induced tissue injury and apoptosis. The MPT was inducedin vitroby incubating freshly isolated rat liver mitochondria in 1 mM Pi with increasing concentrations of calcium. Induction of the MPT was characterized by the calcium-dependent depolarization of mitochondrial membrane potential, release of matrix calcium, and large amplitude swelling. Membrane potential and calcium release were measured with ion-selective electrodes; mitochondrial swelling was monitored spectrophotometrically. Preincubation with either cyclosporine A or TAM prevented, in a dose-dependent manner, the calcium-induced MPT. TAM also inhibited the calcium-induced release of matrix glutathione. TAM caused a time-dependent reversal of both the calcium-induced membrane depolarization and calcium release, suggesting that the effect was on the permeability transition pore and not due to inhibition of the mitochondrial calcium uniport. The results suggest that TAM mimics cyclosporine A to inhibit induction of the MPT and that this activity is not related to the antioxidant properties of TAM.